Ursus arctos subsp. horribilis Ord 1815 ... - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Ursus arctos subsp. horribilis Ord 1815 Synonyms: Ursus arctos subsp. absarokus Merriam 1914; Ursus arctos subsp. andersoni Merriam 1918; Ursus arctos subsp. apache Merriam 1916; Ursus arctos subsp. arizonae Merriam 1916; Ursus arctos subsp. bairdi Merriam 1914; Ursus arctos subsp. bisonophagus Merriam 1918; Ursus arctos subsp. canadensis Merriam 1914; Ursus arctos subsp. candescens C. E. H. Smith 1827; Ursus arctos subsp. cinereus Desmarest 1820; Ursus arctos subsp. crassus Merriam 1918; Ursus arctos subsp. dusorgus Merriam 1918; Ursus arctos subsp. ereunetes Merriam 1918; Ursus arctos subsp. griseus Choris 1822; Ursus arctos subsp. horriaeus Baird 1858; Ursus arctos subsp. hylodromus Elliot 1904; Ursus arctos subsp. idahoensis Merriam 1918; Ursus arctos subsp. imperator Merriam 1914; Ursus arctos subsp. impiger Merriam 1918; Ursus arctos subsp. inopinatus Merriam 1918; Ursus arctos subsp. kennerleyi Merriam 1914; Ursus arctos subsp. kluane Merriam 1916; Ursus arctos subsp. latifrons Merriam 1914; Ursus ... : Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 589, DOI: 10.5281/zenodo.7316519 ...